Nodulation of soybean cultivars with Rhizobium spp. and their response to inoculation with R. japonicum - Pulver, Edward L.; Brockman, F.; Wien, H.C. (1982)
The effect of inoculation with R. japonicum on nodulation, plant growth, and yield of diverse soybean [Glycine max (L.) Merr.] cultivars was studied in Nigeria and Tanzania. Experiments were conducted on soils not previously cropped with soybean. Local cultivars from Nigeria and Indonesia nodulated with indigenous Rhizobium spp. at two sites in Nigeria. Inoculation with several strains of R. japonicum occasionally increased nodule mass of the local cultivars but seldom plant growth or yield. In contrast, U.S. bred cultivars nodulated poorly without inoculation. Large increases in growth and yield were obtained when the U.S. cultivars were inoculated. Similarly, cultivars bred and selected in Tanzania were compatible with native Rhizobium spp.; whereas Bossier (U.S. origin) did not nodulate unless inoculated. The local cultivars used in these experiments were promiscuous and recognized Rhizobium ssp. that were ineffective on U.S. bred material. However, the local cultivars have low yield potentials due to poor agronomic characters. In contrast, the cultivars of U.S. origin are agronomically superior but require inoculation with R. japonicum to realize their yield potential. A breeding program based upon transferring the promiscuous character of some local cultivars to improved U.S. material could produce varieties that do not require inoculation with R. japonicum and still produce high yield.